Modulation of luminescence properties of circularly polarized thermally activated delayed fluorescence molecules with axial chirality by donor engineering - Liu, Shulei; Liu, Songsong; Gao, Yang; Lin, Lili; Wang, Chuan-Kui; Fan, Jianzhong; Song, Yuzhi (Physical chemistry chemical physics : PCCP, 2024)
Multifunctional thermally activated delayed fluorescence (TADF) materials are currently a trending research subject for luminescence layer materials of organic light-emitting diodes (OLEDs). Among these, circularly polarized thermally activated delayed fluorescence (CP-TADF) materials have the advantage of being able to directly achieve highly efficient circularly polarized luminescence (CPL). The simultaneous integration of outstanding luminescence efficiency and excellent luminescence asymmetry factor ( g lum ) is a major constraint for the development of CP-TADF materials. Therefore, on the basis of first-principles calculations in conjunction with the thermal vibration correlation function (TVCF) method, we study CP-TADF molecules with different donors to explore the feasibility of using the donor substitution strategy for optimizing the CPL and TADF properties. The results indicate that molecules with the phenothiazine (PTZ) unit as the donor possess small energy difference, a great spin-orbit coupling constant and a rapid reverse intersystem crossing rate, which endow them with remarkable TADF features. Meanwhile, compared with the reported molecules, the three designed molecules exhibit better CPL properties with higher g lum values. Effective molecular design strategies by donor engineering to modulate the CPL and TADF properties are theoretically proposed. Our findings reveal the relationship between molecular structures and luminescence properties of CP-TADF molecules and further provide theoretical design strategies for optimizing the CPL and TADF properties. The photophysical properties of circularly polarized thermally activated delayed fluorescence (CP-TADF) molecules are regulated by adjusting the type of donors.